Interviewing in action in a multicultural world - Murphy, Bianca Cody; Dillon, Carolyn 1939- (Cengage Learning, 2015)
Text emphasizes and illustrates the relational, interactional, and multicultural nature of contemporary clinical practice. [In the text, the authors] believe that students can best learn when they read about skills, view a variety of seasoned clinicians applying their skills, and practice the skills through role-plays and skill application exercises, receiving feedback from instructors and peers. --Preface.